2022
DOI: 10.3389/fmolb.2022.941653
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs play an important regulatory role in tumorigenesis and tumor progression through aerobic glycolysis

Abstract: Compared to normal cells, cancer cells generate ATP mainly through aerobic glycolysis, which promotes tumorigenesis and tumor progression. Long non-coding RNAs (LncRNAs) are a class of transcripts longer than 200 nucleotides with little or without evident protein-encoding function. LncRNAs are involved in the ten hallmarks of cancer, interestingly, they are also closely associated with aerobic glycolysis. However, the mechanism of this process is non-transparent to date. Demonstrating the mechanism of lncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Breast cancer, stemming from the epithelial tissue of the mammary gland, has witnessed a steady surge in its incidence in recent years ( Ni et al, 2022 ; Guo et al, 2023 ; Patel et al, 2023 ), solidifying its position as the foremost cancer afflicting women ( Hashemi et al, 2023 ). As we delve deeper into the intricacies of this disease, it becomes evident that the Wnt signaling pathway stands at the crossroads of our understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer, stemming from the epithelial tissue of the mammary gland, has witnessed a steady surge in its incidence in recent years ( Ni et al, 2022 ; Guo et al, 2023 ; Patel et al, 2023 ), solidifying its position as the foremost cancer afflicting women ( Hashemi et al, 2023 ). As we delve deeper into the intricacies of this disease, it becomes evident that the Wnt signaling pathway stands at the crossroads of our understanding.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can also participate in multiple signal pathways of cancer (such as p53, AKT, or Notch), epigenetic control, DNA damage, multiple biological functions (e.g., tumor proliferation, metabolism, and apoptosis, etc. ), aerobic glycolysis, and microRNA control, etc., suggesting that they are important players in cancer [ 6 14 ]. Aberrant expression of lncRNAs can affect the occurrence, progress, and drug resistance of cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lncRNAs have been the subject of extensive research recently due to their demonstrated carcinogenic as well as tumor-suppressive functions [ 36 ]. In other words, because lncRNAs play a crucial regulatory role in important physiological processes, they may be used as potential therapeutic targets as well as diagnostic signals [ 37 ]. It is currently known that many lncRNAs have distinct expression patterns in the majority of malignancy types, especially HBV-accused HCC [ 38 ].…”
Section: Introductionmentioning
confidence: 99%